THE INFLUENCE OF ETHNO-CULTURAL PROCESSES ON THE LIFE STYLE OF THE POPULATION OF VAHASHIVOR MOUNTAIN AND MOUNTAIN OLDI - Khurramov Mukhammadsiddiq Sayfiddinovich (Scholar Express Journal, 2023)
The influence of ethnocultural processes on the lifestyle of mountain and submountain inhabitants of Vakhshivor, Surkhandarya region. Vakhshivor mountain and sub-mountain inhabitants of Surkhandarya region are known for their lifestyle and literature. In this article, the impact of ethnocultural processes on the lifestyle of Vakhshivor mountain and submountain inhabitants should be analyzed
Keywords: Surkhandarya; Vakhshivor; mountain; foothills